2019
DOI: 10.3357/amhp.5170.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound Guided Lumbar Puncture and Remote Guidance for Potential In-Flight Evaluation of VIIP/SANS

Abstract: INTRODUCTION: Changes of visual function/neuro-opthalmic structures during spaceflight have been described as visual impairment and intracranial pressure syndrome (VIIP)/spaceflight-associated neuro-ocular syndrome (SANS). Although theories are suggested, the mechanism is unknown. Only indirect measurements of intracranial pressure (ICP) have been performed in spaceflight. Direct determination of in-flight ICP is crucial to understanding VIIP. Current “gold standard” is lumbar puncture (LP). The only direct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Renewed interest in the role of ICP [60][61][62][63][64][65][66][67][68][69] in SANS has led to discussion about the feasibility of performing a lumbar puncture in space despite the obvious logistical and operational challenges to an in-flight invasive procedure. [70][71][72] Non-invasive assessment of ICP have not been reliably validated on earth but ultrasound is available on the ISS and the possibility of ultrasonographic metrics (e.g., optic nerve sheath diameter, CSF in the sheath) remain an area of continued research. Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…Renewed interest in the role of ICP [60][61][62][63][64][65][66][67][68][69] in SANS has led to discussion about the feasibility of performing a lumbar puncture in space despite the obvious logistical and operational challenges to an in-flight invasive procedure. [70][71][72] Non-invasive assessment of ICP have not been reliably validated on earth but ultrasound is available on the ISS and the possibility of ultrasonographic metrics (e.g., optic nerve sheath diameter, CSF in the sheath) remain an area of continued research. Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…POCUS is also used as a method of clinical evaluation in space flights. Astronauts are trained in POCUS and receive health care by medical professionals from the spaceport through complex systems of telecommunications [5].…”
Section: Discussionmentioning
confidence: 99%
“…They found the SVOne (Smart Vision Labs; New York, New York, USA) device was easy to use, could obtain measurements quickly and had excellent intersession reproducibility. Another study by Lerner et al 13 reported on ultrasound guided LP technique with remote guidance for possible inflight performance of LP. The found the technique was successful 9 of 11 times and could be performed in both the fetal and seated lordotic positions.…”
Section: Technology For Studying Sansmentioning
confidence: 99%